A numerical and laboratory study of ice layer growth and freezing characteristics in the vicinity of a vertical ice valve. (August 2017) - Wu, Dongyu; Peng, Jianming; Cheng, Jingqing; Li, Yanliang; Zhang, Xinxin
Highlights: Freezing characteristics in water, seawater and seawater-based mud are compared. Characteristics of upward and downward ice layer growth are investigated. Numerical analysis is conducted and validated by experiments. Solidification front shape and its relationship with pressure retaining are discussed. Abstract: A novel ice valve technique employed in hydrate-bearing sediments coring has attracted more and more attention due to its outstanding ability of pressure maintenance. To make better use of the ice valve, the upward and downward ice layer growth and freezing characteristics in water, seawater and seawater-based mud were investigated, and the potential effects on pressure-retaining performance were discussed. Both numerical method and experiments were conducted to predict the ice layer thickness above and below the direct cooling zone during working time to avoid undesirable freezing in target zones. The freezing process estimated by numerical method was in consistent with the experimental result. It is reliable to predict the ice layer thickness for freezing in a long time. The upward ice layer thicknesses were all shorter than the downward ones. The upward and downward ice layer growth rates after ice valve formation level off to 0.1–0.3 mm/min and a very short distance of 30–40 mm is sufficient to avoid undesirable freezing of hydrate sample or the corer. It is proper to lay out the ice valve below the target zone for a better pressure-retaining performance.